2017
DOI: 10.22219/jpbi.v3i3.4897
|View full text |Cite
|
Sign up to set email alerts
|

Learning the genetics concepts through project activities using Drosophila melanogaster: A qualitative descriptive study

Abstract: Genetics is one of difficult subject for many undergraduate students majoring biology. Authentic-based research is one of learning activity believed could overcome the situation. One of Genetics course that facilitating the students to conduct authentic-based research is Genetics course in Faculty of Mathematics and Natural Science, State University of Malang. The aim of this study was to describe the project research activities in Genetics course, especially the authentic-based research that utilize Drosophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 23 publications
0
12
0
1
Order By: Relevance
“…Various social skills and communication skills are also needed, including the ability to collaborate with others (Ladd et al, 2014;Ouellet, Sabbagh, Bergeron, Mayer, & St-Onge, 2016). In fact, scientific processing skill needs to be empowered in the learning (Erkol & Ugulu, 2014;Fauzi, Corebima, & Zubaidah, 2016;Fauzi & Ramadani, 2017;Gultepe, 2016) and the perception of teachers and parents is very important (Fomichova & Misonou, 2018). From the various explanations, the empowerment of HOTS became one of the goals in the 21 st -century learning process.…”
Section: Introductionmentioning
confidence: 99%
“…Various social skills and communication skills are also needed, including the ability to collaborate with others (Ladd et al, 2014;Ouellet, Sabbagh, Bergeron, Mayer, & St-Onge, 2016). In fact, scientific processing skill needs to be empowered in the learning (Erkol & Ugulu, 2014;Fauzi, Corebima, & Zubaidah, 2016;Fauzi & Ramadani, 2017;Gultepe, 2016) and the perception of teachers and parents is very important (Fomichova & Misonou, 2018). From the various explanations, the empowerment of HOTS became one of the goals in the 21 st -century learning process.…”
Section: Introductionmentioning
confidence: 99%
“…Thomas Hunt Morgan was the first geneticist who used Drosophila melanogaster to uncover various inheritance phenomena (Tolwinski, 2017). The crossing patterns used by Morgan in his research were later adopted as basic procedures in practicum activities in several educational institutions (Fauzi & Ramadani, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Lectures that https://jurnal.unimus.ac.id/index.php/JPKIMIA/index are only based on expository method will further complicate students' understanding of abstract concepts. Conversely, practicum-based learning is still found in a few institutions (Fauzi & Ramadani, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, a variety of active learning strategies (Discovery learning, discussions, research projects, and webbased simulations) are reported to enhance students' understanding of concepts. Learning becomes more meaningful for students to understand and contribute to improving student misconceptions (Alters & Nelson, 2002;Fauzi & Ramadani, 2017;Fiedler et al, 2018).…”
Section: Resultsmentioning
confidence: 99%